Prognostic significance of substage and WHO classification systems in T1 urothelial carcinoma of the bladder. Issue 5 (September 2015) - Fransen van de Putte, Elisabeth E.; Behrendt, Mark A.; Pigot, Garry L.S.; van der Kwast, Theo H.; van Rhijn, Bas W.G.
Abstract : Purpose of review: Treatment of T1 urothelial bladder cancer (T1-BC) is challenging as risk assessment criteria for progression are lacking. Histological grade and T1 substage have been identified as important prognostic factors. Currently, no consensus exists regarding the optimal sub-staging and grading systems for T1-BC. We reviewed recent advances in the various grading and sub-staging systems and their clinical applicability. Recent findings: Stratification by muscularis mucosae invasion is the most explored sub-staging system. Its prognostic value was established by 12/23 (52%) available studies. Importantly, muscularis mucosae identification varied substantially among pathologists. Sub-staging based on diameter of invasive carcinoma [T1 microinvasive and T1 extensive-invasive (T1m/e)] proved a more reproducible system with at least equal prognostic value. However, more study is needed to investigate interobserver variation. For nonmuscle-invasive bladder cancer grading, the 1973 and 2004 WHO classifications both provide independent prognostic information. However, remarkably few studies have investigated their applicability in T1-BC only. The available reports suggest that the 1973 WHO classification is superior to WHO 2004. Summary: If multicenter studies confirm the promising results of T1m/e sub-staging, it may be incorporated in the Internation Union Against Cancer TNM classification system for urinary bladder cancer. More studies are warranted to define the optimal classification system for grade in T1-BC.